(untitled) (Journal of the College of Basic Education, 2024)
The present study aimed to investigate syntactic errors made by EFL learners in composition writing". To achieve the aim of the study, it was assumed that there was no statistically significant differences between the experimental group (which studies writing using the assembly technique (GW and TBT) and that of the control group (which studies writing according to the traditional method). The present study is limited to the second-year College students of English Department, College of Basic Education for the academic year 2023-2024. An eight weeks experiment will be conducted by using -posttest experimental design. Both (the experimental and control groups) were exposed to pre and posttests. Conclusions, recommendations are put forward.